PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA KRISTEN MELALUI METODE CARD SORT PADA SISWA KELAS IV SD NEGERI 163084 KOTA TEBING TINGGI - Junaisih Silalahi (FIP Unimed, 2017)
ABSTRACTThis aim of this research is to improve learning result on Christian Education through card sort method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SD Negeri163084 Tebing Tinggi which amounted to 12 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the card sort method of Christian Education subjects can improve student learning result characterized by increased mastery learning students, namely the first cycle (75%) , cycle II (100 %) and complete learn the clasical equal to 100%.Keywords :Card Sort, Learning Result, Christian Education